CAN-Mediated Oxidative Cyclodehydrogenation of Hexapyrrolylbenzenes - Pandey, Satish K.; Gupta, Vijay; Singh, Ravi P. (Synlett, 2020)
An efficient method for ceric ammonium nitrate mediated synthesis of annularly fused hexapyrrolohexaazacoronene by oxidative cyclodehydrogenation has been reported. The photophysical properties of the representative hexaazacoronene has also been described.
Keywords: ceric ammonium nitrate; coronenes; azacoronene; hexapyrrolylbenzene; oxidative cyclodehydrogenation; MALDI-TOF